Method for eliminating printing cracks in additively manufactured solid solution strengthened nickel-based superalloys

By adding Y elements to solid solution-strengthening nickel-based high-temperature alloys during the powder making stage, the problem of nickel-based high-temperature alloy cracks during laser selection melting is solved, and its mechanical properties are significantly improved, achieving more uniform microscopy Tissue and excellent mechanical properties.

CN115609009BActive Publication Date: 2024-12-17TIANJIN UNIV +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202211140657.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-20
Publication Date
2024-12-17
Estimated Expiration
2042-09-20

AI Technical Summary

Technical Problem

During the melting process of laser selection zone, solid solution-strengthening nickel-based high-temperature alloys are prone to cracks, resulting in a decrease in mechanical properties. Existing methods such as the introduction of doping and mixing of second-phase ceramic particles has problems of powder spherical damage and agglomeration, which affects the plasticity and stability of the alloy. sex.

Method used

During the powder making stage, 0.3-2% Y element was added to the solid solution-strengthening nickel-based high-temperature alloy raw material for alloying, and Y alloying powder was prepared, and the printing and molding was carried out through laser selection melting technology to reduce the number of cracks and improve mechanical properties.

Benefits of technology

It effectively reduces the number of cracks in solid solution-strengthening nickel-based high-temperature alloys, improves its mechanical properties, significantly improves the microstructure state and tensile strength, and meets the strict requirements of aviation manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115609009B_ABST
    Figure CN115609009B_ABST
Patent Text Reader

Abstract

The present invention provides a method for eliminating printing cracks in additive manufacturing of solid solution-strengthened nickel-based high-temperature alloys, comprising the following steps: adding 0.3-2% by mass of Y element to the solid solution-strengthened nickel-based high-temperature alloy raw material for alloying in the powder making stage to prepare Y-alloyed solid solution-strengthened nickel-based high-temperature alloy powder; printing and forming the Y-alloyed solid solution-strengthened nickel-based high-temperature alloy powder by laser selective melting technology to obtain a solid solution-strengthened nickel-based high-temperature alloy. The present invention performs Y element microalloying on the solid solution-strengthened nickel-based high-temperature alloy powder in the powder making stage, effectively reducing the number of cracks in the SLM-printed solid solution-strengthened nickel-based high-temperature alloy, and finally obtaining a laser selective melting-formed component with uniform structure, no printing cracks, and excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of additive manufacturing, and in particular relates to a method for eliminating printing cracks in additively manufactured solid solution strengthened nickel-based high-temperature alloys. Background Art

[0002] Selective laser melting (SLM), as a major technical approach in metal 3D printing technology, overcomes the problems caused by traditional technologies in manufacturing metal parts with complex shapes. It can directly form metal parts that are nearly fully dense and have good mechanical properties. However, the large thermal gradient and repeated remelting of laser selective melting lead to large residual stress in the formed parts and easy cracking. In particular, solid solution-strengthened nickel-based high-temperature alloys containing a large number of high-melting-point metal components (W, Mo, Ta, Co and Cr, etc.) are prone to produce a large number of cracks during the forming process, which seriously reduces the mechanical properties of the formed parts. Therefore, how to control the formation of cracks in laser selective melting of nickel-based high-temperature alloys and improve their mechanical properties has become the key to achieving a wider application of laser selective melting of nickel-based high-temperature alloys.

[0003] To solve the above problems, the most commonly used method to eliminate SLM forming cracks and improve the mechanical properties of printed parts is to introduce ceramic second phase particles (TiC, WC, TiB2, Y2O3, etc.) into the alloy. However, most of the above methods use ball milling or mechanical stirring to mix ceramic second phase particles with metal powders. This process easily destroys the sphericity of the metal powder, which is not conducive to the fluidity of subsequent SLM powder spreading. It is worth noting that due to the different physical and chemical properties between the ceramic second phase particles and the metal matrix and the intense Magranie convection thermal effect during the SLM forming process, the ceramic second phase nanoparticles are very easy to agglomerate and grow in the metal matrix, which will not only weaken its effect as a heterogeneous nucleating agent and strengthening phase, but also greatly reduce the plasticity of the alloy (especially high temperature plasticity), which is not conducive to the stability and durability of the high temperature service of the solid solution strengthened nickel-based alloy. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a method for eliminating printing cracks in additively manufactured solid solution strengthened nickel-based high-temperature alloys, in which Y element microalloying is performed on the solid solution strengthened nickel-based high-temperature alloy powder during the powder making stage, which effectively reduces the number of cracks in the SLM printed solid solution strengthened nickel-based high-temperature alloy and significantly improves the comprehensive mechanical properties of the solid solution strengthened nickel-based high-temperature alloy.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0006] The present invention provides a method for eliminating printing cracks in an additively manufactured solid solution strengthened nickel-based high temperature alloy, the method comprising the following steps:

[0007] Step S1, adding 0.3-2% by mass of Y element to the solid solution strengthened nickel-based high temperature alloy raw material for alloying in the powder making stage to prepare Y alloyed solid solution strengthened nickel-based high temperature alloy powder, wherein the solid solution strengthened nickel-based high temperature alloy is GH3230 or GH3536 or GH3128;

[0008] Specifically, the initial raw materials are placed in a vacuum induction furnace for smelting and cast into a preset ingot, wherein the initial raw materials include a pure single substance block or a master alloy block of a solid solution-strengthened nickel-based high-temperature alloy constituent element and a Y element; and then the preset ingot is prepared into a Y-alloyed solid solution-strengthened nickel-based high-temperature alloy powder;

[0009] Step S2, printing and molding the Y-alloyed solid solution strengthened nickel-based high temperature alloy powder by laser selective melting technology to obtain a solid solution strengthened nickel-based high temperature alloy.

[0010] Preferably, the particle size of the Y-alloyed solid solution strengthened nickel-based high temperature alloy powder prepared in step S1 is 15 to 53 μm.

[0011] Preferably, in step S2, the protective atmosphere during the laser selective melting printing process is argon or nitrogen.

[0012] The present invention has the following beneficial effects:

[0013] The method for eliminating printing cracks in additively manufactured solid solution strengthened nickel-based superalloys provided by the present invention effectively reduces the number of cracks in additively manufactured solid solution strengthened nickel-based superalloys by directly adding Y element in the powder making stage, improves the microstructure state, and greatly improves the mechanical properties of solid solution strengthened nickel-based superalloys. Compared with the prior art, the present invention has the following advantages:

[0014] The present invention directly alloys the solid solution strengthened nickel-based high temperature powder with the Y element during the powder making stage, thereby avoiding the adverse effects of directly adding the second phase on the powder, such as impurity contamination and deterioration of powder fluidity, without the need for complex process design, thereby greatly reducing the number of printing cracks of the solid solution strengthened nickel-based high temperature alloy and improving the comprehensive mechanical properties of the solid solution strengthened nickel-based high temperature alloy.

[0015] In order to achieve excellent comprehensive mechanical properties, the present invention adds Y element to the solid solution strengthened nickel-based high temperature alloy raw material for alloying during the powder making stage. After the addition of Y element, the residual stress generated by the temperature gradient during the forming process is effectively reduced, thereby avoiding the cracking phenomenon of the final solidified structure of the alloy. In addition, during the laser selective melting process, Y element will also form yttrium oxide nanoparticles evenly distributed in the matrix, playing the role of second phase strengthening and significantly improving its mechanical properties.

[0016] In the Y-alloyed solid solution strengthened nickel-based high-temperature alloy powder prepared in step S1 of the present invention, the Y element is evenly distributed without obvious element segregation. The mechanical properties of the solid solution strengthened nickel-based high-temperature alloy parts obtained by additive manufacturing using the Y-alloyed solid solution strengthened nickel-based high-temperature alloy powder meet the stringent requirements of aviation additive manufacturing. The final laser selective melting formed component has a uniform structure, no printing cracks, and excellent mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for describing the embodiments are briefly introduced below. Obviously, the drawings described below are only some embodiments of the embodiments of the present invention.

[0018] Figure 1 (a) is a scanning electron microscope image of a cross section of a Y-alloyed GH3536 nickel-based superalloy powder particle in Example 1, (b) is a local enlarged image of the framed portion in (a), and (c) is an EDS spectrum distribution image of the Y element of the Y-alloyed GH3536 nickel-based superalloy powder in Example 1;

[0019] Figure 2 (a) is an optical microscope picture of GH3536 nickel-based superalloy formed by laser selective melting in comparative example 1, (b) is an optical microscope picture of GH3536 nickel-based superalloy formed by laser selective melting in example 1, and (c) is an optical microscope picture of GH3536 nickel-based superalloy formed by laser selective melting in example 2;

[0020] Figure 3 (a) is a scanning electron microscope image of GH3536 nickel-based superalloy formed by laser selective melting in comparative example 1, and (b) is a scanning electron microscope image of GH3536 nickel-based superalloy formed by laser selective melting in example 1;

[0021] Figure 4 (a) is a transmission electron microscope image of GH3536 nickel-based superalloy formed by laser selective melting in comparative example 1, and (b) is a transmission electron microscope image of GH3536 nickel-based superalloy formed by laser selective melting in example 1;

[0022] Figure 5 This is a comparison chart of the room temperature tensile curves of GH3536 nickel-based high-temperature alloy formed by laser selective melting in Comparative Example 1 and Example 1. DETAILED DESCRIPTION

[0023] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0024] Comparative Example 1

[0025] GH3536 is a typical representative of solid solution strengthened nickel-based high temperature alloys. In this comparative example, GH3536 nickel-based high temperature alloy with original composition is prepared by laser selective melting. The steps are as follows:

[0026] Step S1, under the protective atmosphere of argon, the original composition of GH3536 nickel-based high-temperature alloy powder is formed by laser selective melting equipment to obtain an alloy sample. The forming parameters used are: laser power of 190W, laser scanning speed of 700mm / s, powder thickness of 25um, and melt channel spacing (scanning spacing) of 80um.

[0027] Step S2, grinding and polishing the laser selective melting formed GH3536 nickel-based high-temperature alloy sample obtained in step S1, and performing optical microscope, scanning electron microscope, transmission electron microscope observation and room temperature tensile verification.

[0028] The original composition of GH3536 nickel-based high-temperature alloy after laser selective melting is as follows: Figure 2 As shown in (a), it can be seen that there are a lot of solidification cracks inside. Figure 3 (a) It can be seen that the content of segregated second phase in the original composition of GH3536 nickel-based high-temperature alloy is extremely low, and only some carbides are distributed at the apex of the subgrain; further Figure 4 (a) It can be seen that there are a large number of dislocations in the original composition of GH3536 nickel-based high-temperature alloy, indicating that there is a large amount of residual stress in the alloy structure, which is the main reason for the large number of microcracks in the alloy. Figure 5 The room temperature tensile results show that due to the presence of a large number of solidification cracks in the formed structure of GH3536, the alloy exhibits poor tensile properties.

[0029] Example 1

[0030] This embodiment provides a method for eliminating printing cracks in additively manufactured solid solution strengthened nickel-based high temperature alloys, the method comprising the following steps:

[0031] Step S1: In the powder making stage, 0.78% by mass of Y element is added to the GH3536 nickel-based high-temperature alloy raw material for alloying to prepare Y-alloyed GH3536 nickel-based high-temperature powder.

[0032] Specifically, the constituent elements of the GH3536 nickel-based high-temperature alloy and the pure element block or intermediate alloy block of the Y element are placed in a vacuum induction furnace for melting and cast into a preset ingot, and then the preset ingot is prepared into a Y-alloyed GH3536 nickel-based high-temperature alloy powder.

[0033] Step S2, under the protective atmosphere of argon, the Y-alloyed GH3536 nickel-based high-temperature alloy powder is formed by laser selective melting equipment to obtain a GH3536 nickel-based high-temperature alloy sample. The forming parameters used are: laser power of 190 W, laser scanning speed of 700 mm / s, powder thickness of 25 um, and melt channel spacing (scanning spacing) of 80 um.

[0034] Step S3, grinding and polishing the laser selective melting formed GH3536 nickel-based high-temperature alloy sample obtained in step S2, and performing optical microscope, scanning electron microscope, transmission electron microscope observation and room temperature tensile verification.

[0035] SEM photos of the cross section of Y-alloyed GH3536 high-temperature alloy powder particles and EDS energy spectrum distribution of Y elements are shown in the figure. Figure 1 As shown, it can be seen that the Y element is evenly distributed in the powder without agglomeration.

[0036] Y alloyed GH3536 nickel-based high-temperature alloy after laser selective melting Figure 2 As shown in (b), it can be seen that the internal cracks are greatly reduced, and the number of large-scale cracks that were originally large in number is significantly reduced after Y alloying. Figure 3 (b) It can be seen that the content of segregated second phase in the original composition GH3536 nickel-based superalloy increases significantly, not only distributed along the subgrain boundary, but also there are a large number of spherical second phases inside the subgrain; further from Figure 4 (b) It can be seen that the number of internal dislocations in the Y-alloyed GH3536 nickel-based superalloy is significantly reduced, indicating that the addition of the Y element effectively reduces the residual stress caused by the temperature gradient during the forming process, thereby avoiding the cracking of the final solidified structure of the alloy. At the same time, during the forming process, the Y element, as an oxygen-friendly element, forms the Y2O3 second phase with the O element. Through the strengthening effect of the Y2O3 second phase, the number of cracks in the laser selective melting forming process of the GH3536 nickel-based superalloy can also be effectively reduced.

[0037] Finally, the Y-alloyed laser selective melting GH3536 nickel-based high-temperature alloy prepared in this embodiment was subjected to room temperature tensile verification. Figure 5 It can be seen that the cracks in the GH3536 nickel-based high-temperature alloy are eliminated due to Y alloying, the tensile strength reaches 970 MPa, and the elongation reaches 34.2%, which are significantly higher than the mechanical properties of the original component GH3536 nickel-based high-temperature alloy in comparative example 1.

[0038] Example 2

[0039] This embodiment provides a method for eliminating printing cracks in additively manufactured solid solution strengthened nickel-based high temperature alloys, the method comprising the following steps:

[0040] Step S1: In the powder making stage, 1% by mass of Y element is added to the GH3536 nickel-based high-temperature alloy raw material for alloying to prepare Y-alloyed GH3536 nickel-based high-temperature alloy powder.

[0041] Specifically, the constituent elements of the GH3536 nickel-based high-temperature alloy and the pure element block or intermediate alloy block of the Y element are placed in a vacuum induction furnace for melting and cast into a preset ingot, and then the preset ingot is prepared into a Y-alloyed GH3536 nickel-based high-temperature alloy powder.

[0042] Step S2, under the protective atmosphere of argon, the Y-alloyed GH3536 nickel-based high-temperature alloy powder is formed by laser selective melting equipment to obtain a GH3536 nickel-based high-temperature alloy sample. The forming parameters used are: laser power of 190 W, laser scanning speed of 700 mm / s, powder thickness of 35 um, and melt channel spacing (scanning spacing) of 75 um.

[0043] Step S3, grinding and polishing the laser selective melting formed GH3536 nickel-based high-temperature alloy sample obtained in step S2, and performing optical microscope, scanning electron microscope, transmission electron microscope observation and room temperature tensile verification.

[0044] In this embodiment, the Y-alloyed GH3536 nickel-based high-temperature alloy formed by laser selective melting is as follows: Figure 2 As shown in (c), it can also be seen that the internal cracks are greatly reduced, and the number of large-size cracks, which were originally large in number, is significantly reduced after Y alloying.

[0045] By adjusting the process parameters according to the present invention, the number of internal cracks in the GH3536 sample formed by selective laser melting can be significantly reduced.

[0046] It can be seen from the above technical solutions that the method provided by the present invention for eliminating printing cracks in solution-strengthened nickel-based high-temperature alloys manufactured by additive manufacturing effectively reduces the number of cracks in solution-strengthened nickel-based high-temperature alloys printed by laser selective melting by Y-alloying the solution-strengthened nickel-based high-temperature alloy powder during the powder making process, and improves the mechanical properties of the solution-strengthened nickel-based high-temperature alloy. The present invention directly alloys the solution-strengthened nickel-based high-temperature powder with the Y element during the powder making stage, avoiding the adverse effects of direct addition of a second phase on the powder, such as impurity contamination and deterioration of powder fluidity. It does not require complex process design, greatly reduces the number of printing cracks in the nickel-based alloy, and improves the comprehensive mechanical properties of the nickel-based high-temperature alloy. In addition, other solution-strengthened nickel-based high-temperature alloys with printing crack problems can also be Y-alloyed using the present invention.

[0047] The above embodiments of the present invention are described in detail through examples, but the contents described are only exemplary embodiments of the embodiments of the present invention and cannot be considered to limit the scope of implementation of the embodiments of the present invention. The protection scope of the embodiments of the present invention is defined by the claims. Anyone who utilizes the technical solutions described in the embodiments of the present invention, or who, inspired by the technical solutions of the embodiments of the present invention, designs similar technical solutions within the essence and protection scope of the embodiments of the present invention to achieve the above technical effects, or who makes equal changes and improvements to the scope of application, shall still fall within the scope of protection covered by the patent of the embodiments of the present invention.

Claims

1. A method for eliminating printing cracks in additively manufactured solid solution strengthened nickel-based high temperature alloys, characterized in that: The method comprises the following steps: Step S1, adding 0.3-2% by mass of Y element to the solid solution strengthened nickel-based high temperature alloy raw material for alloying in the powder making stage to prepare Y alloyed solid solution strengthened nickel-based high temperature alloy powder, wherein the solid solution strengthened nickel-based high temperature alloy is GH3230 or GH3536 or GH3128; Specifically, the initial raw materials are placed in a vacuum induction furnace for smelting and cast into a preset ingot, wherein the initial raw materials include a pure single substance block or a master alloy block of a solid solution-strengthened nickel-based high-temperature alloy constituent element and a Y element; and then the preset ingot is prepared into a Y-alloyed solid solution-strengthened nickel-based high-temperature alloy powder; Step S2, printing and molding the Y-alloyed solid solution strengthened nickel-based high temperature alloy powder by laser selective melting technology to obtain a solid solution strengthened nickel-based high temperature alloy.

2. The method for eliminating printing cracks in additively manufactured solid solution strengthened nickel-based high temperature alloys according to claim 1, characterized in that: The particle size of the Y-alloyed solid solution strengthened nickel-based high temperature alloy powder prepared in step S1 is 15 to 53 μm.

3. The method for eliminating printing cracks in additively manufactured solid solution strengthened nickel-based high temperature alloys according to claim 1, characterized in that: In step S2, the protective atmosphere during the laser selective melting printing process is argon or nitrogen.

Citation Information

Cited By

  • Nickel-based superalloy strengthening and toughening laser additive manufacturing method based on power decline

    CN120790957A